Synthesis of acyclovir as an antiherpes-virus drug - Hung, Tran Quang; Thuong, Nguyen Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
A one-pot process for high-yield regioselective synthesis of 9-[(2-hydroxyethoxy) methyl]guanine (acyclovir), an antiherpetic agent, was achieved from guanine via the steps of reacting of N2,N9 -diprotected guanine with 1-acetyl-2-acetylmethoxy-ethyleneglycol in presence of phosphoric acid or polyphosphoric acid. Total yield of product was 59%. The obtained acyclovir meets the standards in the British Pharmacopoeia 2007 (BP2007). Its activity as inhibitor of herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) was evaluated according to the plaque reduction assay method and compared with the standard compound. The synthesized acyclovir showed a similar activity as the control. Keywords: Acyclovir, Herpes simplex virus, Nucleoside, One- pot synthesis.